2015
DOI: 10.1021/jp5118807
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Chemistry via Metadynamics: Benzyl Decomposition Revisited

Abstract: Large polycyclic aromatic hydrocarbons (PAHs) are thought to be responsible for the formation of soot particles in combustion processes. However, there are still uncertainties on the course that leads small molecules to form PAHs. This is largely due to the high number of reactions and intermediates involved. Metadynamics combined with ab initio molecular dynamics can provide a very precious contribution because offers the possibility to explore new possible pathways and suggest new mechanisms. Here, we adopt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 68 publications
(124 reference statements)
2
34
0
Order By: Relevance
“…35,36,39,40,62,63 Although the other fragment measured in this experiment at m/z = 90 has not been unambiguously identified, theoretical work has suggested that it is most likely the fulvenallene molecule. 7,8,41,42 The identification of an H loss channel is corroborated here by the agreement between the Newton diagram in Figure 7 with the angular distribution of signal and by the excellent agreement between the P(E T ) distribution from Song et al, based on measuring the H atom fragment, with our P(E T ) in Figure 8, determined from TOF spectra for the C 7 H 6 counterfragment. We cannot differentiate between the production of fulvenallene and 2-ethynylcyclopentadiene or distinguish which pathway in Figure 1 produces fulvenallene because all of these pathways are energetically very similar.…”
Section: Discussionsupporting
confidence: 82%
“…35,36,39,40,62,63 Although the other fragment measured in this experiment at m/z = 90 has not been unambiguously identified, theoretical work has suggested that it is most likely the fulvenallene molecule. 7,8,41,42 The identification of an H loss channel is corroborated here by the agreement between the Newton diagram in Figure 7 with the angular distribution of signal and by the excellent agreement between the P(E T ) distribution from Song et al, based on measuring the H atom fragment, with our P(E T ) in Figure 8, determined from TOF spectra for the C 7 H 6 counterfragment. We cannot differentiate between the production of fulvenallene and 2-ethynylcyclopentadiene or distinguish which pathway in Figure 1 produces fulvenallene because all of these pathways are energetically very similar.…”
Section: Discussionsupporting
confidence: 82%
“…Three channels have been identified from flash pyrolysis VUV-PIMS experiments, , of which the most important proceeds via the (unobserved) intermediate 4 (Figure ) to produce H atoms and fulvenallene (C 5 H 4 =C=CH 2 ). However, computational studies that are broadly consistent with these findings also predict a plethora of C 7 H 7 RSRs (isomers 5–10 in Figure ) that remain undiscovered. ,, …”
Section: Introductionmentioning
confidence: 54%
“…The PIE(m/z 65) resulting from the thermal cracking of the C 6 H 5 CH 2 radical indicates that there is little (or no) (CH 2 ) 2 C-C≡≡CH present in the pyrolysis of benzyl. It was also predicted by the metadynamics calculations 18 that the initial C 6 H 5 CH 2 radicals could isomerize to a pair of isomeric, dimethylene-cyclopentenyl radicals. The spectroscopic probes of Ref.…”
Section: ′′mentioning
confidence: 92%
“…A recent paper 18 applied metadynamics to the pyrolysis of benzyl. These calculations suggested that both C 5 H 5 and its isomer, (CH 2 ) 2 C-C≡≡CH, are intermediates in the high temperature pyrolysis of benzyl.…”
Section: ′′mentioning
confidence: 99%
See 1 more Smart Citation